Cultivating Islamic Environmental Consciousness: The Case of Al Muharram Eco Mosque in Yogyakarta - Zahra, Fatma Nuraini; Nanda, Dendy H (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2025)
Muslim activists in Indonesia have developed many movements that seek to harmonize Islamic values with ecological awareness. This study explores how muslim-mosque activists understand the environmental crisis and how eco masjid can be the medium for conveying and raising awareness of muslim communities regarding environmental issues. This study applied a qualitative case study approach on mosque communities and muslim-mosque activists in Yogyakarta, i.e. Al Muharram Mosque to gain insight and in-depth results related to the understanding of the environmental crisis and eco masjid. The empirical data were gathered through observation and semi-structured interviews with several muslim activists from the mosque. The ’Eco Masjid’, from its various applications and as a program in general, has demonstrated a positive impact in efforts to increase public environmental awareness. Moreover, mosques can serve as a primary medium for instilling ecological values grounded in the concepts of tawhid (the unity of all creation), stewardship as khalifah on earth (trust and responsibility), and akhirah or mizan (the hereafter and balance). This is supported by the perspectives of mosque activists, who view the environmental crisis as part of humanity’s trust as khalifah, which will become both provision and responsibility in the afterlife. Through more extensive promotion of eco mosque programs, mosques have the potential to become a central medium for disseminating environmental issues, enhancing awareness not only among muslim activists within mosque communities but also generating a broader movement effect within muslim communities across Indonesia. Aktivis muslim di Indonesia telah mengembangkan berbagai gerakan yang berupaya mengharmoniskan nilai-nilai Islam dengan kesadaran ekologis. Salah satu di antaranya adalah gerakan Eco Masjid. Penelitian ini bertujuan untuk menelusuri bagaimana para aktivis Islam memahami krisis lingkungan serta bagaimana eco masjid dapat berperan sebagai medium dalam menyampaikan dan meningkatkan kesadaran masyarakat muslim terhadap isu-isu lingkungan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus komunitas masjid dan aktivis muslim di Yogyakarta, yaitu Masjid Al Muharram, untuk memperoleh pemahaman dan hasil yang mendalam terkait persepsi terhadap krisis lingkungan dan penerapan eco masjid. Data empiris dikumpulkan melalui observasi dan wawancara semi-terstruktur dengan sejumlah aktivis muslim dari masjid tersebut. Hasil penelitian menunjukkan Program Eco Masjid, terbukti memberikan dampak positif dalam upaya meningkatkan kesadaran lingkungan masyarakat. Selain itu, masjid dapat berfungsi sebagai medium utama dalam menanamkan nilai-nilai ekologis yang berdasarkan pada konsep tawhid (kesatuan seluruh makhluk), khalifah di bumi (amanah–khalifah), dan akhirah atau mizan. Hal ini didukung dengan pandangan dari aktivis masjid yang menunjukkan bahwa krisis lingkungan adalah bagian dari amanah manusia sebagai khalifah yang akan menjadi bekal dan tanggung jawab di kehidupan akhirat. Melalui promosi yang lebih masif terhadap program eco masjid, masjid berpotensi menjadi medium utama dalam penyebaran isu-isu lingkungan dan tidak hanya meningkatkan kesadaran di kalangan aktivis muslim di lingkungan masjid, tetapi juga menciptakan efek gerakan di tengah komunitas muslim Indonesia.